ASSESSING THE PERFORMANCE OF GLOBAL SOLAR RADIATION EMPIRICAL EQUATIONS IN SOKOTO, NIGERIA USING METEOROLOGICAL PARAMETERS (Nigerian Journal of Technology, 2018)
In this study, the meteorological parameters measured in Sokoto (12.55o N, 5.15o E) for a period of 10 years (2005-2014) were obtained from the Nigerian Meteorological Agency Sultan Abubakar III International Airport, Sokoto state. The data used include Gunn-Bellani solar radiation, sunshine hour duration, maximum and minimum temperatures, which were analyzed using modified Angstrom models to estimate the monthly mean global solar radiation in Sokoto. Four statistical methods have been used in order to evaluate the results namely; Mean Bias Error (MBE), Mean Percentage Error (MPE), Root Mean Square Error (RMSE) and T-statistic. The standard error (SE) and coefficient of determination (R2) were also obtained for each model. Based on the result obtained models 4 & 5 gave a lower RMSE, and R2 approaches unity, which indicates that there is a good agreement between measured and estimated global solar radiation. http://dx.doi.org/10.4314/njt.v37i2.10